A Panel Data Analysis On The Capital Structure Determinants Of Construction Companies Listed In S&P Bse 500 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: This study examines the determinants of capital structure of firms in Indian Construction sector. An attempt has been made to analyze the determinants of capital structure using firm specific factors like size, tangibility, profitability, tax paid, non debt tax shield, uniqueness, business risk and growth opportunity of construction companies.  Research methodology: This empirical study extends from 2000 to 2019 (20 years) comprising of a total of 49 construction companies listed in S&P BSE 500. Pooled OLS regression has been used to assess the influence of defined explanatory variables on capital structure.  This study helps us to understand how the financial leverage as dependent variable is influenced by eight independent variables. Since the data used under study is cross sectional and longitudinal, Panel data analysis has been done using STATA 13. Before doing the Panel data analysis, the time series data was tested to check the stationarity, heteroscedasticity and auto correlation. Diagnostic test like Hausman test was conducted to check whether fixed effect model or random effect model is appropriate for this study. The study finds that capital structure of Indian Construction sector depends significantly on two determinants like size and uniqueness. Research implications: This study provides insights and understanding of the capital structure determinants of Indian construction sector.